Reliability and validity of an AI-driven smartphone application for measuring countermovement jump height: a comparison with force platform, infrared optical timing, and manual video analysis - Ríos-Gallardo, P. T.; Carranza-García, L. E.; Balsalobre-Fernández, C.; Montalvo, S. (Measurement in Physical Education and Exercise Science, 2025)
This study examined the reliability and validity of a 30 fps artificial intelligence (AI)-based smartphone app for estimating countermovement jump (CMJ) height via bounding box displacement. Eighty male participants from four athletic populations completed two test sessions. Jump height was compared to a criterion force platform (impulse-momentum), an infrared timing system (flight time), and manual high-speed video (240 fps; flight time). Between-session reliability was excellent (ICC =0.90) for the platform, infrared, and manual methods (ICCs =0.96; CVs < 4%), while the AI app showed acceptable reliability (ICC ˜0.90) but greater variability (CV ˜ 7%). Compared to the force platform, AI estimates showed acceptable agreement (ICC ˜0.91), though with systematic underestimation (bias ˜ -3.2 cm), proportional bias, and wider limits of agreement. While highly accessible, the AI app was less precise due to lower frame rate and its alternative measurement approach. Tool selection should consider accuracy, accessibility, and context-specific needs.